Using thoracic ultrasound to detect interstitial lung disease in patients with rheumatoid arthritis: a protocol for the diagnostic test accuracy AURORA study - Robin Christensen; Torkell Ellingsen; Heidi Lausten Munk; Grith Lykke Sorensen; Philip Rask Lage-Hansen; Jesper Rømhild Davidsen; Stefan M W Harders; Bjørk Khaliqi Sofíudóttir (BMJ Open)
Introduction Pulmonary diseases are significant contributors to morbidity and mortality in patients with rheumatoid arthritis (RA). RA-associated interstitial lung disease (RA-ILD) may be prevalent in up to 30% and clinically evident in 10% of patients with RA. Feasible methods to detect concomitant ILD in RA are warranted. Our objective is to determine the diagnostic accuracy of thoracic ultrasound (TUS) for ILD in patients with RA with respiratory symptoms, by using chest high-resolution CT (HRCT) as the reference standard. Further, we aim to evaluate the diagnostic accuracy for the promising blood biomarkers surfactant protein-D and microfibrillar-associated protein 4 in the detection of ILD in this group of patients.Methods and analysis By use of a standardised 14 zone protocol patients suspected of having RA-ILD will undergo TUS as index test performed by a junior resident in rheumatology (BKS), who is certified by the European Respiratory Society in performing TUS assessments. Participants form a consecutive series of up to 80 individuals in total. The anonymised TUS images will be stored and scored by the junior resident as well as two senior rheumatologists, who have received training in TUS, and a TUS-experienced pulmonologist. HRCT will be used as the gold standard for ILD diagnosis (reference standard). The two basic measures for quantifying the diagnostic test accuracy of the TUS test are the sensitivity and specificity in comparison to the HRCT.Ethics and dissemination Data will be collected and stored in the Research Electronic Data Capture database. The study is approved by the Committees on Health Research Ethics and the Danish Data Protection Agency. The project is registered at clinicaltrials.gov (NCT05396469, pre-results) and data will be published in peer-reviewed journals.